Between warrior brother and veiled sister : Islamic fundamentalism and the politics of patriarchy in Iran - Moallem, Minoo (ACLS Humanities E-Book., 2005)
"Minoo Moallem challenges the mainstream stereotypical representation of Islam and Muslims as backward, fanatical, and premodern by showing how Islamic nationalism and fundamentalism are by-products of modernity. Writing with a deep personal and scholarly concern for recent Iranian history, Moallem refers to the gendered notions of brother and sister as keys to understanding the invention of the Islamic ummat as a modern fraternal community. Using magazines, novels, and films, she offers a feminist transnational analysis of contemporary Iranian culture that questions dominant binaries of modern and traditional, West and East, secular and religious, and civilized and barbaric."--Book cover.